Systematic Literature Review: Method Quality as a Determinant of Successful Athletic Learning - Kuncoro, Bagus; Yuliawan, Dhedhy (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Learning in physical education has athletic teaching materials that have a poor image of students. The tendency to dislike athletic material which is considered only limited to running is an obstacle in carrying out athletic learning in elementary schools. So in this literature study, the purpose of this study is to identify, as well as provide criticism and input as well as evidence based on data or research that examines athletic learning. The source of the data for this research was obtained from Mendeley's reference management software with a span of 2015-2021. The process of getting articles with inclusion and exclusion criteria with the keywords learning athletics in elementary schools. The method used is Systematic Literature Review (SLR) with article feasibility test using MMAT. The results of the search for articles in the database obtained 140 articles with screening in 2015-2021 there were 116 which were then entered into the inclusion and exclusion criteria of 26 articles. Furthermore, the feasibility test process with the MMAT was carried out so that 6 articles were obtained which were used as literature in this study. The conclusion of this study is in accordance with the research that has been done and collected from the database that the learning method has an influence on the success of an athletic learning. It can be said that a good method can determine the quality of athletic learning.